Ameliorative effect of Aegle marmelos leaves extract against cisplatin-induced nephrotoxicity and oxidative stress - Ahmad, Rizwan; Mujeeb, Mohd.; Ahmad, Aftab; Anwar, Firoz (Bangladesh Journal of Pharmacology, 2015)
Withdrawn by the Editor